(3TQM GdeYdbGJ GdSHYs - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3GdNWjH GdJHQjRj , CHh RcQjG jMji Hf Ydj Hf HSGe GdTjHGfj, GdNWjH GdJHQjRj,J (B502 (3g` s
(3ChdgG (B:s
(3SCdJfi CMSf Gddg Jhajbc , Cf GdNU dc TQM GdbUGFO GdSHY s
(3BNQgG (B:s
(3eKdgG JNQL GdfUjMg ddbhe adGI ef OhfgG CadGA hgPG BNQ GdSHY GdWhGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3gi GdbUGFO GdSHY (B-(3Ch GdeYdbGJ GdSHYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs